PENGARUH PENGGUNAAN E-MONEY TERHADAP PENCATATAN LAPORAN KEUANGAN DENGAN MODERASI PENGETAHUAN AKUNTANSI - Freddy Kurniawan; Maria Rio Rita (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to examine the effect of the use of e-money on recording financial statements and the influence of moderation of accounting knowledge in the relationship between the use of emoney and recording financial statements.Â The sample used in this study was MSMEs in Argomulyo Salatiga Subdistrict as many as 56 samples were selected through purposive sampling. This study uses primary data in the form of results from distributing questionnaires to owners of Micro, Small and Medium Enterprises (MSMEs). The analysis shows that the use of emoney has a negative significant effect on the recording of financial statements.Â The findings also state that accounting knowledge is able to moderate the relationship between the use of e-money and recording financial statements.